2007
DOI: 10.1007/s10552-007-9020-x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D intake and breast cancer risk in postmenopausal women: the Iowa Women’s Health Study

Abstract: Vitamin D, a prosteroid hormone with anti-proliferative and pro-differentiation activity, is thought to act as a cancer chemopreventive agent. This study evaluated the association between vitamin D intake and breast cancer risk among women in a large prospective cohort study. A total of 34,321 postmenopausal women who had completed a questionnaire that included diet and supplement use were followed for breast cancer incidence from 1986 to 2004. Adjusted relative risks (RR) for breast cancer were calculated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 26 publications
3
84
1
2
Order By: Relevance
“…Variables were entered as covariates in the logistic regression model if (i) including the covariate considerably changed the OR for the main variables of interest (>5% change in the ORs), (ii) if the covariate is a known or potential breast cancer risk factor or, (iii) if the covariate was likely to be associated with the main variable of interest (biological plausibility). OR estimates were both adjusted for time of blood collection in four categories, January-March, April-June, July-September, October-December only and with additional adjustment for first-degree family history of breast cancer (yes/no), number of births (0, 1-2, 3), duration of breast feeding (continuous, in months), age at menarche (<13, [13][14]15), BMI (continuous, in kg/m 2 ) and alcohol consumption (0, 1-18, 18 g ethanol/day). Age at first birth, smoking and education did not affect the estimates considerably and were therefore not included in the final model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Variables were entered as covariates in the logistic regression model if (i) including the covariate considerably changed the OR for the main variables of interest (>5% change in the ORs), (ii) if the covariate is a known or potential breast cancer risk factor or, (iii) if the covariate was likely to be associated with the main variable of interest (biological plausibility). OR estimates were both adjusted for time of blood collection in four categories, January-March, April-June, July-September, October-December only and with additional adjustment for first-degree family history of breast cancer (yes/no), number of births (0, 1-2, 3), duration of breast feeding (continuous, in months), age at menarche (<13, [13][14]15), BMI (continuous, in kg/m 2 ) and alcohol consumption (0, 1-18, 18 g ethanol/day). Age at first birth, smoking and education did not affect the estimates considerably and were therefore not included in the final model.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6] Most of the epidemiologic studies regarding breast cancer risk have assessed the effects of vitamin D only for dietary intake yielding inconsistent results. [7][8][9][10][11][12][13][14][15] However, beside dietary intake, the main source of vitamin D is cutaneous production via sun exposure. Studies assessing the association of breast cancer risk and measures of sun exposure, as a proxy of endogenous vitamin D synthesis, have observed inverse associations.…”
mentioning
confidence: 99%
“…Cohort studies undertaken by Shin et al (122) , McCullough et al (123) , John et al (124) and Robien et al (125) all found some inverse associations between vitamin D intake and/or exposure and breast cancer risk. Shin et al (122) , as part of the Nurses' Health Study (n 88 691), reported no significant associations between total (dietary and supplemental) vitamin D intake and breast cancer incidence in postmenopausal women but did report significant associations when comparing the lowest total vitamin D intake (# 3·75 mg) with the highest vitamin D intake (.…”
Section: Vitamin D and Cancermentioning
confidence: 98%
“…Robien et al (125) reported a weaker non-statistically significant relationship with a RR of 0·89 (95 % CI 0·77, 1·03; P ¼ 0·12) for women with a vitamin D intake of $ 20 mg in the Iowa Women's Health Study. All of these studies are notable due to their large size and prospective cohort design; however, as these were observational studies a causal relationship cannot be confirmed and both studies did not adequately measure sun exposure, which is the main source of vitamin D for most populations.…”
Section: Vitamin D and Cancermentioning
confidence: 98%
“…From a large prospective cohort study of 34 321 postmenopausal women followed for 18 years in the Iowa Women's Health Study, women with vitamin D intake . 800 IU/d had an adjusted risk for breast cancer of 0·89 (weak association) compared with those with vitamin D intake , 400 IU/d (134) . From a population-based casecontrol study in Canada involving 972 newly diagnosed invasive breast cancer and 1135 controls, reduced breast cancer risk was associated with increased sunlight exposure from age 10 to 19 years (135) .…”
Section: Breast Cancermentioning
confidence: 92%